THE PLACE OF EUROPEAN PROTECTIVE MEASURES IN HUNGARIAN CIVIL PROCEDURAL LAW - Dr Suri, Noémi (Zbornik radova Pravnog fakulteta u Novom Sadu, 2026)
The European protective measures created by the European Account Preservation Order is to enable creditors to prevent the subsequent enforcement of the creditor’s claim from being jeopardised or delayed through the transfer or withdrawal of funds held by the debtor in a bank account within the Union. The aim of this paper is to detail the Hungarian rules facilitating the applciation of the European Account Preservation Order in light of the judicial pratice of the last 8 years. To achieve this goal, the first part of this study will elaborate on the conditions for ordering European protective measures, during the examination of which the European and Hungarian regulations applicable to European Account Preservation Orders will be scrutinized in the context of non-contentious procedures. This will be followed by the examination of issues related to legal application in the Hungarian case-law. In summary, it can be concluded that there are significant differences between the conditions of ordering the Hungarian and the European protective measures. While the ordering of a Hungarian protection measure is grounded on presenting the likelihood of the risk of satisfaction, the European Account Preservation Order requires the creditor to prove that the claim enforcement requires urgent legal protection.